Preparation and characterization of amphiphilic polymer coating for marine biofouling control. Issue 1 (March 2020) - Mahto, Lokeshwar; Pal, Dharm
Abstract: Biofouling is a major issue prevalent in marine industry resulting in losses in billions of dollars for repairing and maintenance. Coatings developed to tackle marine biofouling are either toxic towards environment or have shorter lifespan. Amphiphilic block copolymer coatings have gained wide attention recently to mitigate biofouling. In this work, performance of synthesized coating towards biofouling was studied. Hydroxyl terminated polydimethylsiloxane as hydrophobic and chitosan as hydrophilic moiety was used to synthesize the amphiphilic coating. Characterization of the prepared coating using Scanning Electron Microscopy (SEM) showed heterogeneous microstructure. Antifouling performance using egg white as the protein testing probe was done as it simulates the adhesives used by biofouling organism. Resistance to protein adhesion was seen on the surface of the coating. So, the developed environmental-friendly coating can be used effectively for the mitigation of marine biofouling.